2013
DOI: 10.1186/1471-2261-13-55
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of acute coronary syndrome in South Korea: a national survey

Abstract: BackgroundAcute coronary syndrome (ACS) is highly prevalent in Korea and is the third-leading cause of death in Korea; however, the economic cost of ACS on Korean society has not been investigated. This study examined the economic effect of ACS on the Korean population during the period 2004 to 2009.MethodsThe analysis used the cost of illness (COI) framework. Data on direct medical costs, direct non-medical costs, and productivity loss related to ACS morbidity and mortality were included. The Korean National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
11
2
Order By: Relevance
“…Cardiovascular diseases may be increased continuously due to increase in the prevalence of metabolic syndrome over time, since the aging index in Korea is expected to rise from 67.7% in 2010 to 213.8% in 2030. 24 , 25 Therefore, in Korea, ACS is expected to become one of the most common conditions associated with ischemic heart disease, and ACS-related costs will be likely to increase steadily. It is essential to manage ACS early and effectively to prevent ACS-associated mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases may be increased continuously due to increase in the prevalence of metabolic syndrome over time, since the aging index in Korea is expected to rise from 67.7% in 2010 to 213.8% in 2030. 24 , 25 Therefore, in Korea, ACS is expected to become one of the most common conditions associated with ischemic heart disease, and ACS-related costs will be likely to increase steadily. It is essential to manage ACS early and effectively to prevent ACS-associated mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Korean Statistical Information Service (KOSIS), the number of deaths due to AMI (I21) was 19.6 out of every 100,000 Koreans in 2012 [ 3 ]. Also, while the AMI-associated mortality has gradually decreased, the prevalence of AMI is on the rise due to improvement in the early detection and treatment of AMI [ 4 ]. AMI has a heavy socioeconomic burden.…”
Section: Introductionmentioning
confidence: 99%
“…The study also showed that despite a reduction in the percentage of the CVDs mortality cost after the HTP, this reduction was not statistically signi cant compared to that before the HTP, which is not consistent with the ndings of most studies in developed countries. In European countries, more than 60% of the total costs of CVDs attributed to the hospitalization (34,35), while in other studies, it was reported that just about 23% of CVDs costs attributed to the mortality costs in the UK (22) and about 33% in South Korea (36). One of the reasons for this may be due to the low mean age of CVDs mortality and morbidity in developing countries, such as Iran (37).…”
Section: Discussionmentioning
confidence: 99%